CURRENT TRENDS IN THE DEVELOPMENT OF RUNNING SPECIES OF ATHLETICS - Ільченко, Сергій (SWorldJournal, 2023)
Currently, medical and biological studies of children’s health show that studying at school is stressful, and in critical periods of growing up, it is accompanied by a decrease in the adaptation capabilities of the body, the development of a number of di